1994
DOI: 10.1182/blood.v83.3.636.bloodjournal833636
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of tumor cells and hematopoietic progenitor cells into peripheral blood of patients with solid tumors [see comments]

Abstract: Peripheral blood progenitor cells (PBPCs) are increasingly used for autografting after high-dose chemotherapy. One advantage of PBPCs over the use of autologous bone marrow would be a reduced risk of tumor-cell contamination. However, the actual level of tumor cells contaminating PBPC harvests is poorly investigated. It is currently not known whether mobilization of PBPCs might also result in mobilization of tumor cells. We evaluated 358 peripheral blood samples from 46 patients with stage IV or high-risk stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Beyond lack of efficacy, patient data and experimental models revealed that cytotoxic chemotherapy also has paradoxical effects on tumor relapse, promoting metastasis by enhancing vascular permeability and activation of inflammatory pathways, facilitating intra- and extravasation of cancer cells and promoting tumor dormancy ( D'Alterio et al, 2020 ; Shiozawa et al, 2011 ; Brugger et al, 1994 ; Kurppa et al, 2020 ). A series of preclinical studies indicated that antiangiogenic therapies (e.g., targeting VEGFR) can enhance metastasis, potentially by the induction of hypoxic conditions ( Ebos et al, 2009 ; Pàez-Ribes et al, 2009 ).…”
Section: Clinical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond lack of efficacy, patient data and experimental models revealed that cytotoxic chemotherapy also has paradoxical effects on tumor relapse, promoting metastasis by enhancing vascular permeability and activation of inflammatory pathways, facilitating intra- and extravasation of cancer cells and promoting tumor dormancy ( D'Alterio et al, 2020 ; Shiozawa et al, 2011 ; Brugger et al, 1994 ; Kurppa et al, 2020 ). A series of preclinical studies indicated that antiangiogenic therapies (e.g., targeting VEGFR) can enhance metastasis, potentially by the induction of hypoxic conditions ( Ebos et al, 2009 ; Pàez-Ribes et al, 2009 ).…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…Direct evidence for pro-metastatic effects in humans and clinical scenarios is scarce and challenging to demonstrate conclusively. Nevertheless, indirect yet provocative data exists suggesting, for example, that patients receiving cyclophosphamide, taxanes, epirubicine, 5-fluoroacil exhibit suppressed expression levels of miR-488, an inhibitor of epithelial to mesenchymal transition (EMT) ( Li et al, 2011 ) and that CTC numbers as a surrogate for metastatic spread increase post chemotherapy ( Brugger et al, 1994 ). Together, these results highlight the need for a careful examination of risks versus benefits for standard cancer treatments as well as the need to identify the suitable response biomarkers.…”
Section: Clinical Backgroundmentioning
confidence: 99%